2015
DOI: 10.1111/brv.12198
|View full text |Cite
|
Sign up to set email alerts
|

When is dispersal for dispersal? Unifying marine and terrestrial perspectives

Abstract: Recent syntheses on the evolutionary causes of dispersal have focused on dispersal as a direct adaptation, but many traits that influence dispersal have other functions, raising the question: when is dispersal 'for' dispersal? We review and critically evaluate the ecological causes of selection on traits that give rise to dispersal in marine and terrestrial organisms. In the sea, passive dispersal is relatively easy and specific morphological, behavioural, and physiological adaptations for dispersal are rare. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
152
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 146 publications
(167 citation statements)
references
References 146 publications
7
152
0
Order By: Relevance
“…Moreover, we found that migratory phenotypes were more susceptible to diet quality variation, which may result in the non-migratory phenotypes having greater fitness than migratory phenotypes when the nutritional quality of host plants is poor. Our findings support recent calls for a renewed study of migratory and dispersal reaction norms [5] to aid in developing an understanding of the regulation and evolution of migratory and dispersal behaviours [6]. …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Moreover, we found that migratory phenotypes were more susceptible to diet quality variation, which may result in the non-migratory phenotypes having greater fitness than migratory phenotypes when the nutritional quality of host plants is poor. Our findings support recent calls for a renewed study of migratory and dispersal reaction norms [5] to aid in developing an understanding of the regulation and evolution of migratory and dispersal behaviours [6]. …”
Section: Discussionsupporting
confidence: 85%
“…Migration is often viewed as an adaptation to shifting or patchy environments, with migration being induced to allow individuals to seek out better habitats at a given time and life stage [1,5]. However, why and how migration evolves across taxa and the environmental factors that induce migration remain opaque [5,6]. …”
Section: Introductionmentioning
confidence: 99%
“…This deeply affects the ecology, evolution and management of species in upwelling regimes. More larval retention should increase coupling between stock and recruitment, local adaptation and local benefits of marine protected areas as well as vulnerability of marine protected areas to overfishing and other disturbances (Strathmann et al, 2002;Sanford and Kelly, 2011;Burgess et al, 2014Burgess et al, , 2016.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent advances in determining dispersal distances, such as parentage analysis and natural elemental markers, have provided more persuasive evidence that larvae stay closer to home than is widely believed (Burgess et al, 2014(Burgess et al, , 2016Levin, 2006;Morgan, 2014, in press;Swearer et al, 2002;Thorrold et al, 2002Thorrold et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%